Optimization Of Resolution Of Customary Rights Disputes Between The Dayak Agabag Customary Community And PT. KHL Through Deliberation - Vellin Yos Sherly, Melvina; Purwadi, Hari; Mayastuti, Anti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This thesis aims to analyze efforts to resolve disputes through deliberation and the form of legal protection of the customary rights of the Dayak Agabag Indigenous Community with PT.KHL. This study uses an empirical legal research method with a qualitative approach where the research data is obtained through interviews with informants and literature in the form of legislation and data analysis techniques are taken from interviews and literature studies. The results of the study indicate that deliberation is an alternative dispute resolution that results in a mutual agreement, namely the provision of compensation money, UMKM training for the Community and empowering the Dayak Agabag indigenous community to work in the company and build a public facility around the company. As for legal protection for the Dayak Agabag indigenous community issued by the local government specifically for the Dayak Agabag itself, there is no such thing yet, but it is hoped that the government will immediately issue the latest regulations specifically regarding customary rights for the Dayak Agabag indigenous community so that there is strong legal protection and certainty for the Dayak Agabag community.